2010
DOI: 10.1021/nl101894q
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Doping and Subsurface Dopant Reactivation in Si Nanowires

Abstract: Impurity doping in semiconductor nanowires, while increasingly well understood, is not yet controllable at a satisfactory degree. The large surface-to-volume area of these systems, however, suggests that adsorption of the appropriate molecular complexes on the wire sidewalls could be a viable alternative to conventional impurity doping. We perform first-principles electronic structure calculations to assess the possibility of n- and p-type doping of Si nanowires by exposure to NH(3) and NO(2). Besides providin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 57 publications
(96 reference statements)
3
44
0
Order By: Relevance
“…The bonding mechanism is analogous to that previously reported for NH 3 . 28,29 Like in that case, a shallow filled molecular state appears some tenths of eV below the conduction band, creating the conditions for a donor-type doping mechanism (Fig. 4, left panel).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…The bonding mechanism is analogous to that previously reported for NH 3 . 28,29 Like in that case, a shallow filled molecular state appears some tenths of eV below the conduction band, creating the conditions for a donor-type doping mechanism (Fig. 4, left panel).…”
Section: Resultsmentioning
confidence: 79%
“…It is right before achieving the full saturation that a drop in the transparency is observed, indicating a sudden activation of charge carriers in the sample. The Si DNN under study has been demonstrated in the past to show noticeable featureless absorption in the IR (Drude absorption) due to free carriers that can be directly injected 17,28,29 or de-trapped by reactivation of original dopants. 18,29 Data reported in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The passivation mechanism of B dopants has been described by Boarino et al (2001) as the formation of a B-DB (DB = dangling bond), where the extra electron needed by B for its full coordination is provided by the DB in the neighborhoods instead of being extracted by the valence band (Miranda-Durán et al 2010). At the approach of an electron scavenger like the NO 2 molecule, such electron is no longer shared by the DB with the B site, and the last starts behaving as a dopant.…”
Section: Conductivity Of Mesoporous Simentioning
confidence: 99%
“…104 This changed the electrical properties of the silicon surface, as the conductivity was higher when the molecules were in the trans state. Whereas surface transfer doping is already effective for adsorbed molecules, 105 covalent monolayer formation is beneficial for allowing close contact between the dopants and the substrate and for avoiding dopant removal. When the adsorbate molecules are electron-withdrawing, the surface behaves as a p-type semiconductor, whereas electrondonating molecules result in n-type conductivity.…”
mentioning
confidence: 99%